(untitled) (Educational Dimension, 2022)
The research is aimed at the theoretical justification, development and experimental verification of methods of using mobile technologies for teaching students of higher education institutions in the conditions of quarantine caused by the COVID-19 pandemic. The purpose of the study is the adaptation of mobile ICT to distance learning during quarantine. The object of the study is the use of mobile ICT for distance learning. The subject of the study: the use of mobile ICT for distance learning during quarantine. Ukrainian and foreign research on the application of mobile ICT (Audience Response Systems; Mobile Multimedia Authoring Tools development; Mobile Learning Management Systems; Mobile Modeling and Programming Environments; Mobile Database Management Systems) for the training of higher education applicants has been analyzed. The author’s method of using the mobile modeling and programming tool in the Pydroid environment is presented. A comparative assessment of the functionality of five mobile ICT distance learning systems in the conditions of COVID-19 was carried out. A survey of the importance of using mobile ICT for distance learning in quarantine conditions was developed and analyzed.